The Position of Grant Deed for Adopted Children as Juridical Strength of Granting Adoptive Parents' Assets to Adopted Children - Karseno, Imam (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Adoption of children according to the Compilation of Islamic Law is a manifestation of faith that carries a humanitarian mission which is realized in the form of caring for other people as children and is caring for children by nurturing their growth and development by fulfilling all their needs; Grant is one of the ways that adoptive parents can do to adopted children as a form of affection that has been established between the two of them. Because Islam clearly emphasizes that the relationship between adoptive parents and their adopted children does not cause the two of them to have an inheritance relationship, thus an adopted child does not inherit the assets of his adoptive parents; The purpose of this research is to find out the position of the deed of grant made by a Notary which contains grants of the assets of adoptive parents to their adopted children in the conception of legal certainty, and to find out the legal consequences for the deed of grants in the ownership of assets donated by adoptive parents to their adopted children if in the future there will be legal disputes with other heirs; The approach method used is sociological juridical. The data needed in this study includes primary data and secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data obtained was then analyzed qualitatively; The results of this study state that the position of the grant deed made by a Notary for adopted children is normatively that the Grant Deed Number 19/2008 dated 28 April 2008 made before Notary Jhonni M Sianturi, SH is valid and has legal force, because it has fulfilled the requirements in the grant agreement both formally and materially. The legal consequences for the deed of grants granted from adoptive parents to their adopted children, that the perfect proof of an authentic deed (grant) for both parties is intended if a dispute arises before a judge regarding a matter and one of the parties submits an authentic deed, then what stated in the deed has been deemed perfectly proven. If the opposing party denies the truth of the contents of the authentic deed, then he is obliged to prove that the contents of the deed are untrue.Keywords: Adoption; Child; Grant; Notary.